Axial compressive behavior of stainless steel tube confined concrete column piers. (July 2021) - Qiyun, Qiao; Zhaoyuan, Yang; Wanlin, Cao
Abstract: The steel tube confined concrete (STCC) column piers of marine structures have been proposed in recent years. The main advantages of STCC piers include the convenient construction process and improved core concrete strength. This research presents an experimental investigation on stainless steel tube confined concrete (SSTCC) column piers subjected to axial loading. Thirty two specimens were prepared and tested. Test variables included section shape, steel tube thickness, and concrete strength. Failure modes, axial ultimate compressive strength, strain characteristics, rigidity, confinement effect, and ductility were comprehensively investigated. Test results demonstrated that the main failure modes for circular and square specimens were concrete shear failure and steel tube fracture caused by concrete deformation, respectively. The axial compressive ultimate strength was affected by the tube thickness and concrete strength. The ultimate strength increased with the increase in the confinement factor, and the increasing ratio of the circular specimens was five times to that of square specimens. The differences in axial ultimate compressive strength of SSTCC column piers, carbon steel tube confined concrete column piers, and concrete filled steel tube column piers were also analyzed. Increasing tube thickness could increase the ductility and rigidity of the specimens. Moreover, axial ultimate compressive strengths were calculated and discussed based on different calculation models. Highlights: Axial compression behaviors of stainless steel tube confined concrete (SSTCC) column piers were experimentally studied. The differences in failure modes, ultimate strength, strain, rigidity, confinement effect, and ductility were discussed. The differences in axial strength of SSTCC column piers, CSTCC column piers, and CFST column piers were analyzed. Axial ultimate compressive strengths were calculated and compared using different calculation models.